LEARNING FROM THE YEAN AND BOSICO CASE: CAN THE REPARATION MEASURES ORDERED IN THE GUAYUBÍN CASE REALLY PRODUCE POSITIVE CHANGES? - Dupont, Marie-Pier; Rodriguez, Philippe-André (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2013)
This article analyses the likelihood that the Guayubín Case delivered by the Inter-American Court of Human Rights effectively contributes to the improvement of the situation of Haitian migrants in the Dominican Republic and their descendants. It does so by first describing the socio-historical context surrounding the issue. It then looks at the concrete impact of the first decision on the issue, the Yean and Bosico Case, on the situation it addressed. Finally, it attempts to predict which reparations measures of the Guayubín judgment are most likely to be complied with, and whether these measures might have a positive impact.